2014
DOI: 10.1177/0885066614527410
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic–Pituitary Function in Brain Death

Abstract: The Uniform Determination of Death Act (UDDA) states that an individual is dead when "all functions of the entire brain" have ceased irreversibly. However, it has been questioned whether some functions of the hypothalamus, particularly osmoregulation, can continue after the clinical diagnosis of brain death (BD). In order to learn whether parts of the hypothalamus can continue to function after the diagnosis of BD, we performed 2 separate systematic searches of the MEDLINE database, corresponding to the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 62 publications
1
41
2
1
Order By: Relevance
“…The most straightforward explanation for the observation of normouria in patients with BD is that the hypothalamic osmoregulation system continues to function, in at least some patients. The various findings consistent with the preservation of hypothalamic control of the anterior pituitary corroborate this by suggesting preserved blood flow to the area, and suggest some hypothalamic-anterior pituitary function as well, albeit often in the presence of peripheral endocrine insufficiency [6]. Furthermore, anatomical considerations indicate that preserved hypothalamic osmoregulation may be expected in BD.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The most straightforward explanation for the observation of normouria in patients with BD is that the hypothalamic osmoregulation system continues to function, in at least some patients. The various findings consistent with the preservation of hypothalamic control of the anterior pituitary corroborate this by suggesting preserved blood flow to the area, and suggest some hypothalamic-anterior pituitary function as well, albeit often in the presence of peripheral endocrine insufficiency [6]. Furthermore, anatomical considerations indicate that preserved hypothalamic osmoregulation may be expected in BD.…”
Section: Discussionsupporting
confidence: 62%
“…In a recent meta-analysis of 32 studies, concerning 1878 patients with BD, ranging in age from 2 months to 89 years, 925 (49%) were reported to have CDI [6]. The five studies that have published exclusively on pediatric patients, collectively indicated that 145 (52%) of 279 patients had CDI [ 3,4,9,16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, patients who meet the accepted diagnostic criteria for brain death can sometimes have some preserved neurological functioning, particularly hypothalamic functions such as the regulation of free water in the bloodstream (osmoregulation). In a recent review of the clinical literature, Nair-Collins et al 32 found evidence suggesting preservation of hypothalamic function in a substantial proportion of patients declared dead by neurologic criteria. Approximately half of the patients reported in the literature showed evidence suggesting osmoregulation via the regulated secretion of vasopressin (anti-diuretic hormone).…”
Section: Controversies Surrounding the Tests And Pathophysiology Of Bmentioning
confidence: 99%